MAJAS DALAM LIRIK LAGU SOUNDTRACK ANIME KIMI NO NAWA - Putri, Mardwiana; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study discusses the types and analysis of figure of thought meanings contained in the lyrics of anime Soundtrack Kimi no Nawa. This study aims to identify the type of figure of speech and analyze the meaning in the lyrics of the song. The method used in this study is a qualitative descriptive method using the Cognitive Linguistics approach proposed by Lakoff and Johnson. It is found that there are conceptual metaphor, orientational metaphor, ontological metaphor, channel metaphor, simile, part and whole metonymy, causal metonymy, and synecdoche. These figures of thought have meanings related to psychology, expression of feelings, time, events and activity, life, description of objects, distance and space, possession, memory, atmosphere/condition.Key Words : Figure of thought, Song lyrics, Anime Kimi no Nawa, Meaning